CO2-equivalent emissions from European passenger vehicles in the years 1995–2015 based on real-world use: Assessing the climate benefit of the European "diesel boom". (1st February 2019) - Helmers, Eckard; Leitão, Joana; Tietge, Uwe; Butler, Tim
Abstract: A comprehensive overview is provided evaluating direct real-world CO2 emissions of both diesel and petrol cars newly registered in Europe between 1995 and 2015. Before 2011, European diesel cars emitted less CO2 per kilometre than petrol cars, but since then there is no appreciable difference in per-km CO2 emissions between diesel and petrol cars. Real-world CO2 emissions of diesel cars have not declined appreciably since 2001, while the CO2 emissions of petrol cars have been stagnant since 2012. When adding black carbon related CO2 -equivalents, such as from diesel cars without particulate filters, diesel cars were discovered to have had much higher climate relevant emissions until the year 2001 when compared to petrol cars. From 2001 to 2015 CO2 -equivalent emissions from new diesel cars and petrol cars were hardly distinguishable. Lifetime use phase CO2 -equivalent emissions of all European passenger vehicles were modelled for 1995–2015 based on three scenarios: the historic case, another scenario freezing percentages of diesel cars at the low levels from the early 1990s (thus avoiding the observed "boom" in new diesel registrations), and an advanced mitigation scenario based on high proportions of petrol hybrid cars and cars burning gaseous fuels. The difference in CO2 -equivalent emissions between the historical case and the scenario avoiding the diesel car boom is only 0.4%. The advanced mitigation scenario would have been able to achieve a 3.4% reduction in total CO2 -equivalent emissions over the same time frame. The European diesel car boom appears to have been ineffective at reducing climate-warming emissions from the European transport sector. Graphical abstract: Highlights: Diesel cars had much higher CO2 -equivalent emissions than petrol cars until the year 2001. From 2001 to 2015 CO2 -equivalent emissions from new diesel cars and petrol cars became hardly distinguishable. Difference in modelled CO2 -equivalent emissions between 1995 and 2015 and a scenario for the same period avoiding the diesel car boom is negligible. An advanced mitigation scenario would have been able to achieve a 3.4% reduction in total CO2 -equivalent emissions. The European diesel car boom was ineffective at reducing climate-warming emissions from the European transport sector.